Factors influencing microgame adoption among secondary school mathematics teachers supported by structural equation modelling-based research - Wijaya, Tommy Tanu; Cao, Yiming; Bernard, Martin; Rahmadi, Imam Fitri; Lavicza, Zsolt; Surjono, Herman Dwi (Frontiers in Psychology, 2022)
Microgames are rapidly gaining increased attention and are highly being considered because of the technology-based media that enhances students' learning interests and educational activities. Therefore, this study aims to develop a new construct through confirmatory factor analysis, to comprehensively understand the factors influencing the use of microgames in mathematics class. Participants of the study were the secondary school teachers in West Java, Indonesia, which had a 1-year training in microgames development. We applied a quantitative approach to collect the data via online questionnaires through google form. Structural Equation Modeling (SEM) with AMOS software was used to analyze the proposed model. Empirical results confirmed the perceived easy to use and subjective norm influence (PEU & SN) relationship with teachers' microgame usage behaviors and intentions. In this condition, SN was found to have the initial significant influence on behavioral intention (BI), as attitude, BI, and facilitating conditions also correlated with the actual use of microgames. Furthermore, the largest influential factor was BI, with the results subsequently showing that TPACK had no significant influence on the actual use of microgames. This report is expected to help bridge the gap across several previous studies, as well as contribute to the explanation and prediction of the factors influencing the teachers’ mathematical utilization of the study’s program. Besides this, it also helps to increase the use of microgames in teaching and learning activities.